2020
DOI: 10.7324/japs.2020.10813
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 inhibitory activity of marine-derived compounds, aaptaminoids, and benzamide originated from Aaptos aaptos and Acanthaster planci as a potential treatment for atherosclerosis

Abstract: • The 10 leading causes of death in 2015 remained the same as in 2014. Age-adjusted death rates increased for eight leading causes and decreased for one. • The infant mortality rate of 589.5 infant deaths per 100,000 live births in 2015 was not significantly different from the 2014 rate. • The 10 leading causes of infant death in 2015 remained the same as in 2014, although two causes exchanged ranks. This report presents 2015 U.S. final mortality data on deaths and death rates by demographic and medical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…For example, berberine, curcumin, epigallocatechin gallate (EGCG), Welsh onion, quercetin, and methanol extracts of pigeon peas induced the gene expression of PCSK9, which, in turn, increased the gene expression of LDLR and the uptake of LDL-C [ 44 ]. In addition, it was previously reported that a study targeting PCSK9 at the transcriptional level revealed that aaptaminoids and methyl benzoate derivatives inhibited PCSK9 promoter activity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, berberine, curcumin, epigallocatechin gallate (EGCG), Welsh onion, quercetin, and methanol extracts of pigeon peas induced the gene expression of PCSK9, which, in turn, increased the gene expression of LDLR and the uptake of LDL-C [ 44 ]. In addition, it was previously reported that a study targeting PCSK9 at the transcriptional level revealed that aaptaminoids and methyl benzoate derivatives inhibited PCSK9 promoter activity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, circulating PCSK9 levels were reduced upon the daily consumption of marine n-3 polyunsaturated fatty acids (PUFAs) consisting of 38.5% eicosapentaenoic acid (EPA), 25.9% docosahexaenoic acid (DHA), and 6.0% docosapentaenoic acid (DPA) [ 30 ]. The isolated compounds of Aaptos aaptos and Acanthaster planci , and their derivatives, were also found to inhibit the expression of the PCSK9 gene [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several compounds isolated from A. planci were reported to reduce the gene expression of PCSK9 in HepG2 cells. For instance, methyl benzoate and its derivative, N -(2,3-dihydro-1 H -inden-2-yl)-2-methoxybenzamide inhibited the gene expression of the PCSK9 [ 25 ]. Similarly, aaptamine, a compound isolated from other marine organisms, Aaptos aaptos was also reported to inhibit the transcriptional activity of PCSK9 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, methyl benzoate and its derivative, N -(2,3-dihydro-1 H -inden-2-yl)-2-methoxybenzamide inhibited the gene expression of the PCSK9 [ 25 ]. Similarly, aaptamine, a compound isolated from other marine organisms, Aaptos aaptos was also reported to inhibit the transcriptional activity of PCSK9 [ 25 ]. Several other compounds such as berberine, originally isolated from a Chinese herb Huanglian, also reduced the gene expression of PCSK9, and in turn, increased the gene expression of LDLR and uptake of LDL-C by liver cells [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation